Evaluation of cinnamaldehyde and cinnamic acid derivatives in microbial growth control. (July 2019) - Malheiro, J.F.; Maillard, J.-Y.; Borges, F.; Simões, M.
Abstract: The conspicuous absence of novel and effective strategies to control microbial growth, both in the food and healthcare industries and evidence of increasing microbial resistance to conventional biocides has led to a search for novel antimicrobials and growth prevention strategies. In this study, 15 phytochemicals and derivatives, structurally-related to cinnamic acid and cinnamaldehyde, were assessed for their effects on the growth of Escherichia coli, Staphylococcus aureus and Enterococcus hirae. Their effects were compared to seven commonly used biocides (hydrogen peroxide, sodium hypochlorite, chlorhexidine, cetyltrimethylammonium bromide, triclosan, o -phthalaldehyde and lactic acid). All phytochemicals and derivatives increased lag phase and culture doubling time of the tested bacteria. Cinnamic acid and other derivatives inhibited bacterial growth. The MIC of cinnamaldehyde was comparable to o -phthalaldehyde and sodium hypochlorite and lower than hydrogen peroxide and lactic acid. The effect of methyl trans -cinnamate on bacterial growth was more evident against Gram-negative bacteria. It also inhibited quorum sensing in Chromobacterium violaceum . The effect of phytochemicals against sessile bacteria was low: <1 log CFU.cm −2 . Inhibition of quorum sensing and of bacterial growth supports the fact that phytochemicals are an interesting source of antimicrobials with potential use as biocides or more likely as additives to improve the efficacy of current biocidal formulations and preservative systems. Graphical abstract: Image 1 Highlights: Phytochemicals can be used as biocides or additives for novel formulations. Cinnamic acid and some derivatives can inhibit planktonic and sessile growth. Cinnamaldehyde MBC against S. aureus comparable to commonly used biocides. Methyl trans -cinnamate inhibits QS and modifies adhered bacteria susceptibility.